Licensing and innovation with imperfect contract enforcement. Issue 2 (29th January 2018) - Gilbert, Richard; Kristiansen, Eirik Gaard
Abstract: Licensing promotes technology transfer and innovation, but enforcement of licensing contracts is often imperfect. We model contract enforcement as a game with perfect information but probabilistic enforcement and explore the implications of weak enforcement on the design of licensing contracts, the conduct of firms, and market performance. An upstream firm develops a technology that it can license to downstream firms using a fixed fee and a per‐unit royalty. Strictly positive per‐unit royalties maximize the licensor's profit if competition among licensees limits joint profits. With imperfect enforcement, the licensor lowers variable royalties to avoid cheating. Although imperfect contract enforcement reduces the profits of the licensor, weak enforcement lowers prices, increases downstream innovation, and in some circumstances can increase total economic welfare.